Efektifitas Penggunaan Mobile Application Marriott Bonvoy dalam Peningkatan Kepuasan Tamu di Sheraton Bandung Hotel & Towers - Verselly, Shelli; Iskandar, Hari (Jurnal Ilmiah Pariwisata, 2023)
This research aims to determine the effect of using the Marriott Bonvoy mobile application on guest satisfaction at the Sheraton Bandung Hotel & Towers. This type of research is quantitative descriptive with a simple regression analysis method. The data collection technique is by distributing questionnaires using probability sampling techniques. The population in this study was 34,304 people, with a sample using the Slovin formula of 395 respondents. The research results show that the use of the Marriott Bonvoy mobile application at the Sheraton Bandung Hotel & Towers has a significant positive impact on guest satisfaction. This is because using the Marriott Bonvoy mobile application can facilitate a fast reservation process, loyalty program, personalization of preferences, check-in/check-out efficiency, local information, and real-time feedback, creating an efficient, personalized, and enjoyable stay environment. . Suggestions for Sheraton Bandung Hotel & Towers involve active promotional campaigns, staff training, dedicated loyalty programs, personalization of guest preferences, direct feedback encouragement, as well as special offers through the app to increase usage and guest satisfaction. Keywords: Mobile Application, Customer Satisfaction